Speechifying : the words and legacy of Johnnetta Betsch Cole - Cole, Johnnetta B. (Duke University Press, 2023)
"Speechifying collects the most important speeches of Dr. Johnnetta Betsch Cole-noted Black feminist anthropologist, the first Black female president of Spelman College, former director of the Smithsonian Institute's National Museum of African Art, and former chair and president of the National Council of Negro Women. A powerful and eloquent orator, Dr. Cole demonstrates her commitment to the success of Historically Black Colleges and Universities, her ideas about the central importance of diversity and inclusion in higher education, the impact of growing up in the segregated South on her life and activism, and her belief in public service. Drawing on a range of Black thinkers, writers, and artists as well as Biblical scripture and spirituals, her speeches give voice to the most urgent and polarizing issues of our time while inspiring transformational leadership and change. Speechifying also includes interviews with Dr. Cole that highlight her perspective as a Black feminist, her dedication to public speaking and "speechifying" in the tradition of the Black church, and the impact that her leadership and mentorship have had on generations of Black feminist scholars"--